2006
DOI: 10.1039/b609658c
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the reactivity of oximate α-nucleophiles with electrophilic phosphorus centers. Relevance to detoxification of sarin, soman and DFP under mild conditions

Abstract: Following a potentiometric determination of the relevant pKa values of the (R1R2)C=NOH functionality, the second order rate constants (k(Ox)) for reaction of a large set of oximate bases with two model organophosphorus esters, i.e. bis-(4-nitrophenyl)phenylphosphonate (BNPPP) and bis-(4-nitrophenyl)methylphosphonate (BNPMP), and three toxic compounds, i.e., sarin (GB), soman (GD) and diisopropylphosphorofluoridate (DFP), in aqueous as well as a 30 : 70 (v/v) H2O-Me2SO mixture have been measured. The correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 83 publications
1
44
0
Order By: Relevance
“…The special interest in study of the reactivity of typical representatives of this class of reagents, oximate ions (Ox -), is first of all due to the fact that effective antidotes are found among them: re-activators of the acetylcholinesterase inhibited by organophosphorus compounds, the search for which is being vigorously pursued at the moment [4]. There is no doubt that the level of biological activity of the antidotes is directly connected with the high reactivity of Ox -ions [4][5][6][7]. Detailed kinetic analysis of their behavior suggests that the nucleophilicity of Ox -ions cannot be described in terms of a single Brönsted equation [4][5][6][7].…”
mentioning
confidence: 99%
“…The special interest in study of the reactivity of typical representatives of this class of reagents, oximate ions (Ox -), is first of all due to the fact that effective antidotes are found among them: re-activators of the acetylcholinesterase inhibited by organophosphorus compounds, the search for which is being vigorously pursued at the moment [4]. There is no doubt that the level of biological activity of the antidotes is directly connected with the high reactivity of Ox -ions [4][5][6][7]. Detailed kinetic analysis of their behavior suggests that the nucleophilicity of Ox -ions cannot be described in terms of a single Brönsted equation [4][5][6][7].…”
mentioning
confidence: 99%
“…These calculations assumed that the Brønsted linear equation holds for the kinetic scheme for reactivation shown in equation 20. It should be noted, however, that a recent study showed that above pK a = 9 the corresponding Brønsted plot deviates from linearity for nucleophilic displacements of oximates at the P atom of a variety of OPs, a behavior that was attributed by the authors to an increase in solvation 158 . Yet, the observed break in the linear curve could also be explained by a change in the rate-limiting step of the addition-elimination S N 2 reaction.…”
Section: Biochemical and Physiological Characteristicsmentioning
confidence: 81%
“…[1][2][3][4][5][6][7][8][9][10][11][12] These reactions have been reported to proceed through a concerted mechanism or a stepwise pathway depending on the nature of the nucleophiles and substrates. [2][3][4][5][6][7][8][9][10][11][12] Alkaline ethanolysis of aryl dimethylphosphinates has been concluded to proceed through a pentacoordinate intermediate, its formation being the rate-determining step (RDS) on the basis that s o constants result in significantly better Hammett correlation than s À constants.…”
Section: Introductionmentioning
confidence: 99%